Penerapan Konsep Persamaan Diferensial Biasa Pada Pemodelan Tali Penahan Jembatan Gantung - Sri Wulandari Pratiwi; Arjudin Arjudin; Nani Kurniati; Sripatmi Sripatmi (Griya Journal of Mathematics Education and Application, 2021)
bridge from the concept of ordinary differential equations and to determine solving differential equations and capitalizing suspension bridges, with the suspension bridge in Gerung, West Lombok is a modeling. The type of this research is Quantitative research with development methods literature. The subject in this research retaining ropes on suspension bridges. The data collected in the form of journals or articles from various related sources model of the retaining rope on a computed suspension bridge analyzed and concluded by the researcher through data analysis techniques by using the type of research triangulation principle and theoretical triangulation based on the results of data analysis, it was found that differential equations can be applied to modeling suspension bridges through first-order ordinary differential equations with the form of capitalization equations with the solution , with the interval in . The Gerung suspension bridge has its retaining rope modeling solution is , in 12 right suspensions at each hose in the interval the related variable is the height of the retaining rope and x the independent variable is the distance from the lowest restraint to the rope to be measured.